Industrialisierungsprozesse in Polen - Förster, Horst (ERDKUNDE, 1974)
The basic spatial pattern of industry in Poland at the present time is the result of the differing characteristics of the primary milieu and the processes of development which have occurred under various economic and political systems. The processes of industrial concentration have at the same time led to urbanisation processes which have decisively altered the economic and social structure of Poland. Three important periods can be recognised in the historical development process of the industrial urban agglomerations. The first period of early industrial growth from the middle of the last century to 1914 was characterised by a relatively fast rate of spatial concentration. This development led, because of the different political territories then involved, to later disproportionality in economic potential. The second phase, between the Wars, was one of partly politically determined stagnation. The third period, that of development since 1945, has been moulded by the basic principles of a socialist planned economy. Because of this, certain economic and organisational tendencies can be assigned to the individual planning periods. Whereas the time up to 1949 was one of reconstruction, the First Six Year Plan (1955) was characterised by relatively high rises in productivity and investment activity. Significant changes in the structure, size and type of production locations first occurred, however, only in the succeeding Five Year Plans, which also attempted to overcome inherited spatial disparities.